Smart Locking System for RON95 (R95-ATech) by Implementing Motor and Claw Application - Saadon, Imad Yusuf; Rasida Norjali, (Progress in Engineering Application and Technology, 2024)
The implementation of Radio Frequency Identification, RFID locking mechanism on nozzle pump represents an innovative approach to improve access control measures over subsidized fuel, RON95. The following report details the development, execution and assessment of sophisticated locking system that incorporates RFID technology through the utilization of motor and mechanical components. RON95 is a cost-effective means for Malaysian consumers to fuel their vehicles. Although Malaysians have benefited financially from the system, it has been taken advantage of by citizens from other countries, particularly Singaporeans. In order to resolve this problem, the study suggests implementing a locking mechanism that utilises recognition technologies. The access is only available to Malaysian nationals and may only be obtained by registering their personal information for the access where in this case, the Unique Identification UID of their identification card, IC. The goal is to mitigate the unauthorised utilisation of subsidised RON95 petrol, guaranteeing that only intended beneficiaries reap the advantages of this governmental endeavour. The system also integrates with alarm system which triggered for specific reason which could prevent from unwelcomed action from be taken that could damage the unit.